An assessment of radial haemolysis in the detection of rubella antibody. - Gee, B (1978)
The results obtained by radial haemolysis in the detection of antibodies to rubella virus compared well with those obtained by haemagglutination inhibition. Radial haemolysis is unaffected by non-specific inhibitors. The sera do not therefore require pretreatment and the results are less equivocal. Radial haemolysis appears to be as sensitive as immunofluorescence and floatation centrifugation. It is possible to examine large numbers of sera with a considerable saving of time compared with the traditional haemagglutination technique. Rheumatoid factor may cause interference in radial haemolysis. Immune sera may be recorded as non-immune. This interference can be removed by 2-mercaptoethanol or reduced by heating sera at 60 degrees C for 20 minutes.